Teacher Leaders and Student Achievement: can the dots be connected? - Calderone, Sommer; Kent, Andrea M.; Green, Andre M. (Revista Eletrônica de Educação, 2018)
Abstract This study was designed to determine the effects of teacher leadership on student achievement in middle school math and science. Participants were 173 8th grade students, and eight teachers — four of whom were identifed as teacher leaders. The experimental groups were comprised of students who were instructed by teachers identifed as teacher leaders; and the control groups were comprised of students instructed by teachers not identifed as teacher leaders. Each experimental and control group was compared using the Explorer test results to determine equivalence between groups. An ANOVA performed on End of Quarter Test data in advanced and non-advanced math and science revealed a signifcant difference in both the advanced science and math groups; teacher leaders are positively correlated with higher scores of the advanced math and science groups. No signifcant difference was found between the experimental groups and control groups in either non-advanced math or science classes; teacher leaders did not signifcantly impact the scores of the non-advanced math and science groups. Keywords: Teacher leadership, Middle school, Math, Student achievement. References ACT. Explorer Test. 2013. Retrieved from http://www.act.org/explorestudent/ ANDREWS, D.; CROWTHER, F. Parallel leadership: A clue to the contents of the “black box” of school reform. International Journal of Educational Management, 16,152-159, 2002. doi:10.1108/09513540210432128 BASS, B. M.; RIGGIO, R. E. Transformational leadership (2nd ed.). Mahwah, NJ: Lawrence Erlbaum, 2006. BEACHUM, F.; DENTITH, A. M. Teacher leaders creating cultures of school renewal and transformation. The Educational Forum, 68, 276-286, 2004. doi:10.1080/00131720408984639 BILL AND MELINDA GATES FOUNDATION. Learning about Teaching: Initial Findings from the Measures of Effective Teaching Project. Seattle, Washington: Author, 2010. Retrieved from http://www.metproject.org/downloads/Preliminary_FindingsResearch_Paper.pdf BRUGGENCATE, G.; LUYTEN, H.; SCHEERENS, J.; SLEEGERS, P. Modeling the influence of school leaders on student achievement: How can school leaders make a difference? Education Administration Quarterly, 48, 699-732, 2012. doi:10.1177/0013161X11436272 COBURN, C. E.; RUSSELL, J. L. District policy and teachers’ social networks. Educational Evaluation and Policy Analysis, 30(3), 203-235, 2008. CURTIS, R. Finding a new way: Leveraging teacher leadership to meet unprecedented demands. Washington, D.C.: The Aspen Institute, 2013. DANIELSON, C. Teacher leadership that strengthens professional practice. Alexandria, VA: Association for Supervision and Curriculum Development. 2006. DANIELSON, C. The many faces of leadership. Educational Leadership, 65(1) 14-19, 2007. ELLIOTT, R.; KAZEMI, E.; LESSEIG, K.; MUMME, J.; CARROLL, C.; KELLEY-PETERSEN, M. Conceptualizing the work of leading mathematical tasks in professional development. Journal of Teacher Education, 60, 364-379, 2009. GARET, M. S.; PORTER, A. C.; DESIMONE, L.; BIRMAN, B. F.; YOON, K. S. What makes professional development effective? Results from a national sample of teachers. American Educational Research Journal, 38, 915-945, 2001. GIGANTE, N. A.; FIRESTONE, W.A. Administrative support and teacher leadership in schools implementing reform. Journal of Education Administration, 46, 302-331, 2008. HARRISON, C.; KILLION, J. Ten roles for teacher leaders. Educational Leadership, 65, 74-77, 2007. JACOBS, A. Examining the relationship between student achievement and observable teacher characteristics: Implications for school leaders. International Journal of Educational Leadership Preparation, 7, 1-13, 2012. Retrieved from http://cnx.org/content/m44965/latest/ LEITHWOOD, K.; JANTZI, D. The relative effects of principal and teacher sources of leadership on student engagement with school. Education Administration Quarterly, 35, 679-706, 1999. doi:10.1177/0013161X99355002 ROBINSON, V.; LLOYD, C.; ROWE, K. The impact of leadership on student outcomes: An analysis of the differential effects of leadership types. Education Administration Quarterly, 44, 635-674, 2008. doi:10.1177/0013161X08321509 SNELL, J.; SWANSON, J. The essential knowledge and skills of teacher leaders: Asearch for a conceptual framework. Paper presented at the annual meeting of the American Education Research Association, New Orleans, LA, 2000. WAHLSTROM, K. L.; YORK-BARR, J. Leadership: Support and structures make the ifference for educators and students. Journal of Staff Development, 32, 22-25, 2011. http://eric.ed.gov/?id=EJ941373 WATERS, T.; MARZANO, R. J.; MCNULTY, B; MID-CONTINENT REGIONAL EDUCATIONAL LAB., A. C. Balanced Leadership: What 30 Years of Research Tells Us about the Effect of Leadership on Student Achievement. A Working Paper, 2003. WHITAKER, T. Informational teacher leadership - The key to successful change in the middle school level. NASSP Bulletin, 79, 76-81, 1995. doi:10.1177/019263659507956712 YORK- BARR, J.; DUKE, K. What do we know about teacher leadership? Findings from two decades of scholarship. Review of Educational Research, 74, 255-316, 2004.